China in the International Liberal Order: Global Debates and Perspectives from South America - Rubiolo, Florencia (2023)
The debate around the role of China in the current international order continues to split the waters within the theoretical discussions of International Relations. Is Beijing seeking to establish a new order? Or, starting from the relative weakness of the international liberal order, is it redefining some principles, but still helping to sustain it? The main objective of the article is to analyze the role of the People's Republic of China in the international order, and the implications that it may have in the definition of its role in the regional order of South America. The methodological approach is qualitative, with an in-depth review of secondary sources to construct the central theoretical discussion, and then using primary statistical and secondary bibliographic and documentary sources for the analysis of three specific cases: Argentina, Brazil and Chile. It is concluded that the role of China at a global level and in Latin America must still be understood within the current international order, where it plays a role in sustaining it, particularly from the multilateral global governance perspective.